2014
DOI: 10.1002/cphc.201402327
|View full text |Cite
|
Sign up to set email alerts
|

Water OH Bond Activation by Gas‐Phase Plutonium Atoms: Reaction Mechanisms and Ab Initio Molecular Dynamics Study

Abstract: A thorough description of the reaction mechanisms, taking into account different possible spin states, offers insights into the gas-phase reaction of plutonium atoms with water. Two possible reactions (isomerization and dehydrogenation) are presented. These reactions are found to be exothermic, with the best thermochemical conditions observed for the dehydrogenation reaction at around 23.5 kcal mol(-1). The nature of the chemical-bonding evolution along the reaction pathways are investigated by employing vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…A positive H(r) implies the closed‐shell interaction, whereas negative H(r) is regarded as the standard of covalent character . The H(r) standard was proven to be very appropriate to characterize the nature of a bond for heavy‐atom systems …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive H(r) implies the closed‐shell interaction, whereas negative H(r) is regarded as the standard of covalent character . The H(r) standard was proven to be very appropriate to characterize the nature of a bond for heavy‐atom systems …”
Section: Resultsmentioning
confidence: 99%
“…[9,29] The H(r)standard was proven to be very appropriate to characterize the nature of a bond for heavy-atom systems. [30][31][32] For the sake of simplicity, only a few main stationary points are analyzed as example.…”
Section: Bonding Analysismentioning
confidence: 99%
“…Using theory, several investigations into the reaction mechanisms of actinide atoms with small molecules have been performed using different calculation methods. In fact, detailed reaction processes have been obtained for the following systems: Pu + H 2 O, 29 PuO 2 + H 2 , 30,31 Th + NH 3 , 32 and Th + (Th 2+ ) + H 2 O. 33 These studies demonstrated the reaction mechanisms and electronic structures along the minimum energy reaction pathways as well as the potential energy proles.…”
Section: Introductionmentioning
confidence: 92%
“…2,3 Therefore, over the last few decades, the reaction of plutonium with small molecules in the gas phase has attracted signicant attention both in experimental [1][2][3][4][5][6][7][8][9][10][11][12] and theoretical studies. [13][14][15][16][17][18][19][20][21] In addition, the reaction of plutonium with water which can provide some insight into the corrosive mechanism of steam on nuclear fuel is a more imperative and challenging research eld.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent theoretical study, 21 the mechanisms and molecular dynamics of the reaction of gas phase Pu atom with H 2 O were investigated by DFT computation. The reaction pathways shown in the following equations were determined.…”
Section: Introductionmentioning
confidence: 99%